Thermodynamics of Morphogenesis: Beading and Branching Pattern Formation in Diffusion-Driven Salt Finger Plumes - Hisashi Ozawa; Sayaka Murayama-Ogino; Axel Kleidon (Entropy)
Spontaneous pattern formation is a universal phenomenon that occurs in purely physical systems, biology, and human societies. Salt fingering due to differential diffusion of heat and salt in seawater is a typical example, although the general principle that governs pattern formation remains unknown. We show through simple experiments injecting a salt solution into a sucrose solution of equal density that a salt finger exhibits characteristic pattern transitions depending on the injection flow rate. When the rate increases, a linear finger starts meandering, branching, and multiple branching, whereas when the rate is decreased, it produces a beading pattern. These morphological instabilities and associated pattern formation are caused by a local accumulation of kinetic energy that minimizes the flow resistance and maximizes the energy dissipation in the final steady state. We suggest that this energy accumulation mechanism governs a wide variety of pattern formation phenomena in non-equilibrium systems, including morphogenesis of abiotic protocells.